Digital Literacy Among Young Adults in Romania - MOCANU, Florinela (Management Dynamics in the Knowledge Economy, 2018)
The present study has the purpose to analyze the digital behavior and the digital literacy among young adults in Romania. The first part of the paper investigates the literature studies regarding the essay’s subject, exposing concepts as reference group, social inclusion, groupthink, social façade, gadget and digital literacy. We are investigating also the perceived risks in the internet usage and the self-perception in handling digital devices. The research included three focus groups applied on young people from the 20-29 years old age cluster, urban residence in Romania. The main results exposed that both social media and technology have a central role in young people’s lives, by helping them ease communication, get to information and stay entertained. In choosing the platforms they use, it’s important the friendly interface, the range of activities they can do and the user profile in general, age and interest related. Results show that the participants perceive technology as having both positive and negative impact. They report that they do not perceive any major risks in using social media and that this matter wasn’t considered an issue when using a digital platform until now. The participants have a positive attitude about their digital skills and are declared open to learn new features. An interesting subject that was brought to attention was the children exposure to inappropriate information in using technology and the concern they raised about the subject.